2020
DOI: 10.1044/2020_jslhr-19-00269
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Monaural Asymmetry and Target–Masker Similarity on Binaural Advantage in Children and Adults With Normal Hearing

Abstract: Purpose For colocated targets and maskers, binaural listening typically offers a small but significant advantage over monaural listening. This study investigated how monaural asymmetry and target–masker similarity may limit binaural advantage in adults and children. Method Ten Mandarin-speaking Chinese adults (aged 22–27 years) and 12 children (aged 7–14 years) with normal hearing participated in the study. Monaural and binaural speech recognition thres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…It is not surprising that the hearing status in the nonimplanted ear limited segregation of competing speech for the Baseline condition. Interestingly, Liu et al (2020) found significant performance asymmetry across ears for SRTs in NH children when target and masker speech were colocated and no talker sex cues were available. They found no binaural benefit over the better-ear alone, similar to observations with the present unilaterally deaf CI users.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not surprising that the hearing status in the nonimplanted ear limited segregation of competing speech for the Baseline condition. Interestingly, Liu et al (2020) found significant performance asymmetry across ears for SRTs in NH children when target and masker speech were colocated and no talker sex cues were available. They found no binaural benefit over the better-ear alone, similar to observations with the present unilaterally deaf CI users.…”
Section: Discussionmentioning
confidence: 99%
“…Recognition of target speech in the presence of masker speech was measured using the matrix-style test materials from the Closed-Set Mandarin Speech corpus (Tao et al 2017), which has been used in several studies by Fu and colleagues (Tao et al 2018; Liu et al 2019; Chen et al 2020; Liu et al 2020). The stimuli consisted of 5 categories (Name, Verb, Number, Color, and Object), each with 10 words.…”
Section: Methodsmentioning
confidence: 99%